ACHIEVING SIMPLICITY: A CONSIDERATION OF A SYSTEMATIC APPROACH. (May 2020) - Pilz, F.; Vajna, S.; Schabacker, M.
Abstract: Design principles from the field of design engineering require that a product be designed as unambiguous, safe and simple as possible. Simplicity results on the one hand from an objective product-relevant side, on the other hand from the experience and knowledge of the user. A product that is perceived as simple by one person may seem complicated to another. From this, the questions arise, with which attributes simplicity can be described and how these are to be captured. In this paper, an evaluation system for the subjective attributes of simplicity is created using the fuzzy sets approach.